Long-term exposure to ambient air pollution portends a higher risk of coronary plaque vulnerability and instability in patients with acute coronary syndrome: an optical coherence tomography study. (14th October 2021) - Montone, R A; Camilli, M; Russo, M; Del Buono, M; Termite, C; La Vecchia, G; Rinaldi, R; Iannaccone, G; Gurgoglione, F; Trani, C; Niccoli, G; Crea, F
Abstract: Background: Air pollution is an emerging key player in determining the residual risk of coronary events. However, pathophysiological mechanisms linking air pollution and coronary events have been not adequately investigated. Purpose: We assessed the relationship between exposure to air pollutants and mechanisms of coronary instability evaluated by optical coherence tomography (OCT) in patients with acute coronary syndrome (ACS). Methods: ACS patients undergoing OCT imaging were retrospectively selected. Mechanism of culprit lesion instability was classified as plaque rupture (PR) or intact fibrous cap (IFC) by OCT, and the presence of macrophage infiltrates (MØI) and thin-cap fibroatheroma (TCFA) at the culprit site was also assessed. Based on each case's home address, exposure to several pollutants was evaluated, including particulate matter 2.5 (PM2.5), particulate matter 10 (PM10), and carbon monoxide (CO). Only patients with >2 years of available data on air pollution exposure prior to ACS were enrolled. Results: We included 136 patients [median age 67.0 years (56.2–76.0), 104 (76.5%) male]. Sixty-six patients (48.5%) had PR as mechanism of plaque instability. Patients with PR were exposed to significantly higher PM2.5 levels compared to IFC, and PM2.5 was an independent predictor for PR (OR=1.133, 95% CI [1.020–1.258], p=0.019). Moreover, exposure to higher levels of PM2.5, PM10 and CO was an independent predictor for the presence of TCFA, while PM2.5 and CO levels predicted the presence of MØI. Interestingly, PM2.5, PM10 and CO levels were positively and significantly correlated with serum levels of C-reactive protein. ROC curves were constructed to assess the ability of PM2.5 to predict the presence of plaque rupture, TCFA or MØI. The AUC for PM2.5 to predict plaque rupture was 0.62 (95% CI: 0.52–0.71, p=0.018), for TCFA was 0.71 (95% CI: 0.61–0.80, p<0.001) and for MØI was 0.80 (95% CI: 0.71–0.88, p<0.001). Using a PM2.5 cut-off value of 13.40 μg/m 3, the sensitivity and specificity for MØI were 81% and 66%, respectively. Conclusions: We provide novel insights into the missing link between air pollution and increased risk of coronary events. In particular, exposure to higher concentrations of air pollutants is a risk factor for vulnerable plaque features and for plaque rupture as mechanism of coronary instability mediated by systemic and local plaque inflammation. Of importance, the thresholds of air pollutants that predicted the presence of vulnerable plaque features are far lower than commonly accepted safety thresholds used to start preventive measures for public health, suggesting that further efforts are needed in order to reduce the adverse effects on the cardiovascular system. FUNDunding Acknowledgement: Type of funding sources: None.